Модель сбора информации в кластерной беспроводной сенсорной сети - Галкин, П. В. (ХНУРЕ, 2019)
The paper analyzes the cluster structure of wireless sensor networks. The optimal position of the aggregator in the piconet is determined at the site of the intercluster gateway. This position allows the aggregator to communicate with at least two within the piconet. Aroaches for managing information flow in clusters, piconets and between them are proposed.